2019
DOI: 10.1016/j.redox.2019.101098
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin disruption by lipoxidation and electrophiles: Role of the cysteine residue and filament dynamics

Abstract: The intermediate filament protein vimentin constitutes a critical sensor for electrophilic and oxidative stress, which induce extensive reorganization of the vimentin cytoskeletal network. Here, we have investigated the mechanisms underlying these effects. In vitro, electrophilic lipids, including 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) and 4-hydroxynonenal (HNE), directly bind to vimentin, whereas the oxidant diamide induces disulfide bond formation. Mutation of the single vimentin cysteine residue (Cys32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(148 citation statements)
references
References 65 publications
(120 reference statements)
9
138
1
Order By: Relevance
“…For instance, in fibroblasts, vimentin is particularly affected during senescence as it simultaneously suffers from direct carbonylation, as well as HNE and AGE adductions. Vimentin has been shown to be prone to binding of HNE and it has been observed that senescent primary fibroblasts express on their cell surface vimentin presenting lipid peroxidation adducts . Indeed vimentin is subject to various nonenzymatic modifications, mostly oxidative in nature, which may be involved in the regulation of the vimentin network under stress conditions.…”
Section: Protein Oxidative Modifications In Senescent Fibroblasts Andmentioning
confidence: 99%
“…For instance, in fibroblasts, vimentin is particularly affected during senescence as it simultaneously suffers from direct carbonylation, as well as HNE and AGE adductions. Vimentin has been shown to be prone to binding of HNE and it has been observed that senescent primary fibroblasts express on their cell surface vimentin presenting lipid peroxidation adducts . Indeed vimentin is subject to various nonenzymatic modifications, mostly oxidative in nature, which may be involved in the regulation of the vimentin network under stress conditions.…”
Section: Protein Oxidative Modifications In Senescent Fibroblasts Andmentioning
confidence: 99%
“…Vimentin plays key roles in essential cell functions such as division and migration and contributes to cellular structural support and plasticity and organelle positioning. In addition, recent reports have unveiled its complex interplay with other cytoskeletal systems [1,2] and its involvement in redox sensing [3,4], regulation of gene expression, [5] or protection of the nucleus and DNA from damage [6]. Moreover, biophysical techniques are providing high resolution information on the mechanics and dynamic performance of the vimentin network, with a clear impact on the physical properties of cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In cells, vimentin is subjected to an exquisite regulation, both by transcriptional and posttranscriptional mechanisms relying on a plethora of posttranslational modifications, including phosphorylation, glycosylation, SUMOylation, as well as non-enzymatic processes, like oxidative modifications [4,16]. In particular, modifications of the vimentin single cysteine residue, C328 in human vimentin, play a key role in filament assembly in vitro and network remodeling in cells [3,4,17]. Oxidative modifications of C328 disrupt in vitro filament formation in a manner dependent on the structure of the modifying moiety [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations